Congress "Chemical-pharmaceutical and Biological Preparations: Pharmaceutical and Clinical Development in Accordance with the Rules of the EAEU" - article Editorial (Разработка и регистрация лекарственных средств)
The Congress "Chemical and Biological Drugs: Pharmaceutical and Clinical Development in Accordance with the EAEU rules" will be held in Moscow on September 22 at the Sechenov University Congress Center. The theme of the event traditionally covers all life stages of a medicinal product, from development to post-registration studies of drugs.